Dendritic ZSM-5 zeolites as highly active catalysts for the valorization of monoterpene epoxides (2024)
Dendritic ZSM-5 zeolites were investigated in the isomerization of monoterpene epoxides, including limonene-1,2-epoxide (LE), α-pinene epoxide, and β-pinene epoxide, which yields high-value compounds used in fragrances, cosmetics, and pharmaceuticals. The fresh catalysts were thoroughly characterized using XRD, Ar physisorption, pyridine-FTIR, TEM, FTIR/DTBPyr, and 27Al MAS NMR. In comparison with conventional and hierarchical ZSM-5 materials, the dendritic zeolite with a crystallization time of 4 days (d-ZSM-5/4d) was the most active material, with a turnover frequency value of 4.4 min−1 for LE isomerization. Likewise, remarkable yields of dihydrocarvone (DHC, 63%, 70 °C, 2 h), campholenic aldehyde (72.4%, 70 °C, 5 min), and myrtanal (47.7%, 50 °C, 5 min) were obtained with this material that exhibited the largest mesopore/external surface area (360 m2 g−1), showing also the narrowest mesopore size distribution. A direct relationship was observed between the TOF values and the concentration of external Brønsted acid sites, showing the presence of strong steric/diffusional limitations that are greatly overcome with the dendritic zeolites. The lower reactivity of trans-LE compared to cis-LE was attributed to the larger steric hindrance of the oxygen atom. Exploration of the solvent influence revealed that the reaction rate of LE was favored by non-polar solvents, while highly selective DHC formation occurred in the solvents of medium polarity. The d-ZSM-5/4d sample was shown to be robust because catalytic activity could be completely recovered by air calcination.